2019
DOI: 10.1007/s40843-019-9433-4
|View full text |Cite
|
Sign up to set email alerts
|

Conductive metallic filaments dominate in hybrid perovskite-based memory devices

Abstract: Organic−inorganic hybrid perovskites (OHPs) are well-known as light-absorbing materials in solar cells and have recently attracted considerable attention for the applications in resistive switching memory. Previous studies have shown that ions can migrate to form a conductive channel in perovskites under an external voltage. However, the exact resistance mechanism for Ag or halogens which dominate the resistive behavior is still controversial. Here, we demonstrate a resistive switching memory device based on A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…PL maps with emission wavelengths of 800-810 nm for MCP-FA 0.92 MA 0.08 and 715-815 nm for Tra-FA 0.9 -MA 0.1 are presented in Fig. 6c, d, respectively [8,44]. For the MCP-FA 0.92 MA 0.08 film, the range in the main PL peak was wide, which proved the absence of the second phase.…”
Section: Figurementioning
confidence: 81%
“…PL maps with emission wavelengths of 800-810 nm for MCP-FA 0.92 MA 0.08 and 715-815 nm for Tra-FA 0.9 -MA 0.1 are presented in Fig. 6c, d, respectively [8,44]. For the MCP-FA 0.92 MA 0.08 film, the range in the main PL peak was wide, which proved the absence of the second phase.…”
Section: Figurementioning
confidence: 81%
“…It means that high stability of defects was critical for better endurance. Z. Xu et al have indicated that the small radius of Cs + is able to help the hindering of I − movement in two respects [ 32 ]. On one hand, the incorporation of Cs + in the perovskites results in cell lattice shrinkage, which thus requires a higher activation energy for I − hopping.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the greatest potential of ReRAM is that many switching materials could be selected. Recently, in addition to its photovoltaic applications, organic–inorganic metal halide perovskite has been demonstrated as an active layer in ReRAM cells, showing tunable and remarkable memory properties and flexibility [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Based on the various material systems of perovskite, the constituent tuning provides an influential factor in controlling the memory property; [ 34 ] but most of the research about the memory application of the three-dimensional (3D) perovskites is still focused on MAPbI 3 [ 22 , 23 , 25 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this information, it is evident that large differences exist in the resistive-switching properties of different switching materials. Unfortunately, the intrinsic mechanism behind the resistive-switching behavior of all-inorganic QDbased RRAM devices is yet to be determined, though some mechanisms have been suggested, such as filamentary conduction [29,30] and charge trapping and detrapping [31]. Therefore, extensive studies should be conducted concerning the resistive-switching properties of memory devices based on all-inorganic QDs, especially with respect to developing new switching materials and establishing an intrinsic mechanism to provide a practical solution for commercialization.…”
Section: Introductionmentioning
confidence: 99%